Naming of the victims of Nazi medicine - Matuchansky, Claude (The Lancet (British edition), 2017)
I read with great interest the Perspectives piece by Philip Ball (June 3, p 2182),1 who reported on the Science and Suffering exhibition at the Wiener Library for the Study of the Holocaust and Genocide in London. He rightly highlighted the goal of discovering the names and life stories of victims of the Nazi-era medical experiments. He stated that some of their 15 000-perhaps as many as 27 000-names are projected onto the library's wall.